Антропоморфні фігурки трипільського поселення Небелівка - Бурдо, Н.Б. (Археологія і давня історія України, 2014)
Представлено результати аналізу унікальної
збірки антропоморфних статуеток небелівської локально-хронологічної групи Трипілля ВІІ з мегапоселення Небелівка, матеріали з розкопок якого зберігаються в НФ ІА НАНУ. Статья посвящена описанию уникальной коллекции антропоморфной пластики, полученной при
исследовании эпонимного памятника небелевской
локально-хронологической группы мега-поселения
Небелевка. Проанализированы статуэтки, полученные при раскопках остатков жилища А 9, святилища
и собранные на поверхности памятника. Охарактеризованы технологические, морфологические и стилистические особенности небелевских статуэток, их археологический контекст. Анализ небелевской терракоты
показывает ее полное соответствие антропоморфной
пластики трипольской культуры этапа В II. Полученные данные существенно пополняют источниковедческую базу антропоморфных изображений конкретных локально-хронологических групп Триполья. This article presents the description of a unique
collection of anthropomorphic figurines obtained during
the research at the eponymous mega-settlement
of Nebelivka local and chronological group. Analyzed
are the figurines excavated at the dwelling A9, a sanctuary
and found on the surface at the site, which are
stored in the collections of the Institute of Archaeology.
Described are the technological, morphological,
and stylistic peculiarities of statuettes from Nebelivka
and their archaeological context. Analysis of these terracottas
shows that they totally correspond to anthropomorphous
plastics of Trypillia culture BII stage. The data obtained significantly supplement the source base of anthropomorphous depictions of concrete local and chronological groups of Trypillia.